IJCM_206A: Building a demographic, developmental and environmental surveillance site in an urban slum and resettlement colony in Delhi, India: processes, engagement, and challenges - a SWOT analysis - Basu Saurav; Sharma Nandini; Rao Shivani; Singh M M; Malik Shikha Taneja (Wolters Kluwer Medknow Publications, 2024)
Background: Demographic, developmental and environmental surveillance sites (DDESS) enable accurate and prospective health-related data collection amongst socioeconomically disadvantaged populations that facilitate health planning and interventions. Objectives: We explored the community-engagement strategies, enablers, and barriers in building a DDESS site in an urban slum and resettlement colony-based field practice area of a government medical college in Delhi. Methodology: We conducted qualitative research through SWOT analysis that identified both internal (strength and weaknesses), and external (opportunities and threats) factors in building the DDESSS. Informal interviews with multiple stakeholders including researchers, field investigators, project staff, local medical officers, resident doctors, community health workers, local residents, and leaders were conducted. Results: The themes related to SWOT analysis were identified as: (1). Internal factors - Strengths (a). Pre-existing linkage with the community especially provision of comprehensive primary care services (b). Establishment of community-advisory boards (c). Community needs assessment (2): Internal factors - Weaknesses (a). Perceived lack of individual benefit in residents (b). Dissatisfaction with functioning of existing health services (c). Inadequate digital literacy among senior staff hindering generation and adoption of health data to meet population healthcare needs (c) Concerns over privacy in questions related to socioeconomic status and mapping of the area. (3). External factors - Opportunities (a). Employment of field workers belonging to the community to demonstrate trust and build confidence (b). Outreach health services including noncommunicable screening camps, and child vaccination. (4). External factors - Threats (a). Inefficient functioning of health system such as out-of-stock drugs, delayed vaccination, unavailability of diagnostic services in existing primary health facilities. (b). ensuring availability of adequate human and financial resources beyond the project period. (c) dominance of CABs by influential individuals or groups. Conclusion: Garnering community support and active community engagement enable the process of establishment of medical college based DDESS sites.